Penambahan Bubuk Kopi Pada Produk Pewarna Henna Untuk Rambut Beruban - Ponco Nofian Mustoro (Garina, 2022)
Hair dye is a cosmetic used in hair cosmetology that serves to restore the original color of the hair, cover gray hair, or create other colors. The purpose of this study is to develop hair dye based on henna powder and coffee powder as a natural coloring. The methods used in this study are observation methods, literature, experiment, documentation, questionnaires, and R&D. The results of research for hair dye product that have been added henna powder and coffee powder with the right dose indicate that, the composition of these two ingredients can be used as an ingredient in the manufacture of hair dye for gray hair. The color produced from henna powder and coffee powder is black, with a cream texture and rather coarse particles. The distinctive aroma of coffee is produced from coffee powder which is one of the natural ingredients in coloring and aroma. The author's suggestion for this study is the need for a lab test to determine the expiry time on hair dye products made from henna powder and coffee powder, and a way to improve the texture of the product to be smoother again so that it is easier to apply it to the hair.